The calcimimetic R-568 prevents podocyte loss in uninephrectomized ApoE-/- mice - Koleganova, Nadezda; Piecha, Grzegorz; Pradel, Antje; Geldyyev, Aman; Ritz, Eberhard; Schmitt, Claus P.; Groß-Weissmann, Marie-Luise (American journal of physiology. Renal physiology, 2013)
Calcimimetics are indicated for secondary hyperparathyroidism in chronic kidney disease, and some data have suggested their protective role for progression of renal damage. We aimed to evaluate whether a calcimimetic can slow the progression of kidney damage in uninephrectomized apolipoprotein E (ApoE)-deficient (ApoE−/−) mice. To this end, we compared its effect with that of calcitriol. Male ApoE−/− mice (12 wk old) were randomized to undergo sham operation (sham) or unilateral nephrectomy (UNX) and subsequently received the calcimimetic R-568 (4 μg·kg−1·day−1), calcitriol (0.03 μg·kg−1·day−1), or vehicle intraperitoneally. Glomerular number and volume, damage indexes (glomerular, vascular, and interstitial), and glomerular (podocytes, mesangial, and endothelial) cell number and volume were assessed in perfused kidneys after a 12-wk treatment period. Lower numbers of podocytes per glomerulus were observed in the UNX + vehicle group compared with the sham group, and this was prevented in the UNX + R-568 group but not in the UNX + calcitriol group. In parallel, albuminuria was higher in the untreated UNX group compared with the sham group, and the increase was prevented in the UNX + R-568 group. Interstitial fibrosis was more prevalent in the vehicle-treated UNX group compared with the sham group, and this was prevented in the UNX group treated with R-568 and less effectively with calcitriol treatment. In all UNX groups, the weight of the residual kidney was significantly higher compared with all sham groups. No differences were observed in serum ionized calcium and systolic blood pressure between the groups. The calcimimetic R-568 prevented interstial fibrosis and podocyte loss after uninephrectomy in ApoE−/− mice. Minor renal dysfunction, lack of secondary hyperparathyroidism, and hypertension in this model support the hypothesis of direct effects of this compound on glomerular cells.
Im Titel ist "-/-" nach ApoE hochgestellt
Gesehen am 10.02.2021